A study on school bully in Malaysia / Atiqah Mohamed @ Mohamad Saim, Musliha Md. Yusuf and Mohd. Farham Md. Shalleh - Mohamed @ Mohamad Saim, Atiqah; Md. Yusuf, Musliha; Md. Shalleh, Mohd. Farham (2006)
This research is aimed to give exposure on the issue of school bully in Malaysia. Our objectives are to discuss some relevant points on the types of school bully, the factors, and the effects and also on the measures in controlling school bully. There are many types of school bully which have been identified by experts. These include physical bullying, verbal bullying, racist bullying, and also emotional bullying. The causes of school bully could range from psychological and environmental factor which will be discussed further in our next chapter. While the effects of school bully may be vary from long term effects and also short term effect, be it on the victims as well as on the bullies. With regard to the measures in controlling school bully, we will discuss on the basis of legal and social perspectives. These will include the approaches that have been taken by the United States, Scotland and Australia which can be adopted into Malaysian law. We will also discuss further on the roles of family and schools as measures in combating school bully. We also managed to get feedback from the students of SMK Sultan Salahuddin Abdul Aziz Syah, Shah Alam regarding their awareness on school bully. Questionnaires have been distributed and the results can be referred in our last chapter, which is Findings. Interviews also have been conducted with three different respondents to get their view and opinion on school bully. In conclusion, it is hoped that our research will help in giving awareness to the public on the prevalence of school bully and as a medium to educate them in dealing with this crucial issue.